Digitization indices - measurement, comparison and discussion. - Dumoulin, David; Schmitz, Christine; Zeiner, Stephan (NWV Verl., 2018)
The paper offers an introduction to digitization and indices in general, with an overview and evaluation of eight examples, the selection of which helps to represent the scope and range of the aforementioned attributes. The discussion further offers an examination of indices as descriptors and components of the concept of territorial capital, including the connections and interdependencies within. Against that background, a comparative analysis of the digitization strategies of the German state of Bavaria and Austria is presented. with the two regions being selected based an their general similarity. This circumstance serves to underscore the differing approaches in addressing the digitization process. These practical examples help demonstrate the rote of indices as part of the wider discussion surrounding digitization, as well as its state-sanctioned implementation.
Keywords: Standort; Digitalisierung; Technische Infrastruktur; Entwicklungsstand; Index; Internationaler Vergleich